Cultural Adaptation and Life Satisfaction of Expatriate Teachers in Private Schools in Azerbaijan - Mehdiyeva, Kayra (My University, 2026)
This study is a qualitative research study on the cultural adaptation processes of expatriate teachers working in private schools in Azerbaijan, by investigating their professional well-being, challenges, and coping strategies. While the number of private schools in the country is rapidly growing, there has been little research so far on the experiences of expatriate teachers in these schools. Semi-structured interviews were conducted with nine expatriate teachers, and the data obtained were analysed using thematic coding methods. The trustworthiness of the research was ensured through peer review and memoing. The findings indicate that the process of cultural transition is a gradual process that develops positively over time. The research findings showed that expatriate teachers face various challenges in the initial stages of transitioning to a new culture, including language differences, differences in student behaviour, and the expectations of the students’ parents. However, the findings also revealed that expatriate teachers overcome these challenges through supportive relationships, leadership support, and the academic success of their students. The study concludes with implications for school administrators and policymakers to better support the integration and retention of expatriate staff.
Keywords: Expatriate Teachers; Cultural Adaptation; Cross-Cultural Adjustment; Private Schools; International Education; Teacher Well-Being; Professional Well-Being; Teacher Challenges